Cultural rights and freedoms of the individual enshrined in the Constitution abroad: a comparative analysis - Birmanova, A.I.; Balgimbekova, G.U.; Lavnichak, A. (KSU publ., 2020)
In the scientific article on the basis of studying the legislation of foreign countries the comparative legal analysis of legal regulation of cultural rights is given. The article analyzes the impact of universal and regional international treaties that enshrine cultural human rights on the constitutional legislation of a number of European States. The inclusion of cultural rights in the category of constitutionally enshrined is one of the features of the development of the legislative process in many countries of the world since the second half of the XX century. The purpose of the article is to show the development of «cultural law», and the task is to reveal the concept of cultural law on the example of the analysis of the legislation of the CIS countries and some Western European countries. Attention is drawn to the fact that the constitutions of European countries do not directly provide for the right of access to cultural property as a set of legal institutions, but a number of laws contain certain elements of this right. The methodological basis of this scientific work was dialectical, systemic, comparative legal, normative and other methods of cognition. The conclusion is formulated that the task of each state is not only their detailing in the national legislation, but also practical implementation for the purpose of preservation and rational use of the cultural heritage. It is concluded that the study of foreign experience of legislative regulation of cultural rights provides ample opportunities for its use in practice.
Keywords: constitution; cultural human rights; cultural values; European countries; legal institutions; guarantees; legal documents; legislation